Pengaruh Pengungkapan Key Audit Matters dan Audit Tenure Terhadap Audit Report Lag dengan Corporate Reputation sebagai Variabel Moderasi - Putri Adelia Syaharani; Ridha Azka Raga (LP3M INSTITUT KH YAZID KARIMULLAH, 2026)
This study aims to examine the effect of key audit matters (KAM) disclosure and audit tenure on audit report lag, with corporate reputation as a moderating variable, in non-cyclical consumer sector companies listed on the Indonesia Stock Exchange in 2022–2024. The sample was selected using a purposive sampling technique, resulting in 78 companies with a total of 234 observations. Data were analyzed using multiple linear regression and moderated regression analysis. The results show that KAM disclosure has no significant effect on audit report lag, audit tenure has a negative and significant effect on audit report lag, and corporate reputation is not proven to moderate the influence of both on audit report lag.